A STUDY OF MOTIVATIONAL DRIVERS FOR PROFESSIONAL GROWTH AMONG NURSES (The Research of Medical Science Review, 2025)
Nurses often experience a lack of recognition for their work, which diminishes their self-esteem and job happiness. The perception of nursing as a low-status profession by the general population exacerbates feelings of dissatisfaction and disempowerment. Underappreciation, unfavourable working conditions, and a lack of opportunity for professional development are the main connected issues that demotivate nurses in Pakistan to pursue their professional development. These factors foster an atmosphere in which nurses feel overworked and underappreciated, which can result in burnout and a desire to quit the field. The study aims to assess the Lack of motivation among staff nurses towards their personal and professional growth. A convenient sampling was employed. A semistructured interview was conducted to collect rich data. The researcher performed interviews in compliance with the 2018 Ethical Guidelines of the British Educational Research Association (BERA) to uphold the ethical consideration of my research. Prior to performing the interview, informed consent was sought from the participant. Data is analysed through thematic analysis. the study came to five key conclusions that contribute to nurses demotivation which are inefficient workload distribution, salary concerns, Lack of emotional quotient of the leaders under whose supervision nurses work, moreover they are given minimal opportunities for their professional growth.